Regeneração natural do componente arbóreo após a mortalidade de um maciço de taquara em um fragmento de floresta ombrófila mista em Lages - SC - Santos, Kristiana Fiorentin dos; Ferreira, Tiago de Souza; Higuchi, Pedro; Silva, Ana Carolina da; Vandresen, Paula Burigo; Costa, Adriano da; Spada, Grasiela [UNESP]; Schmitz, Veronica; Souza, Franciele de (Centro Pesquisas Florestais, UFMS, 2015)
The present study aimed to analyze the floristic and structural descriptors of tree species natural regeneration in a forest sector with synchronized bamboo (Merostachys multiramea Hackel) die-off (CT) and an adjacent area with continuous canopy cover (ST) in an araucaria forest fragment in the municipality of Lages, Santa Catarina state. A total of 14, 5x5m, plots (six plots in CT sector and eight in ST sector) were allocated, where all tree species regenerative individual with circumference at breast height smaller than 15cm and height higher than 25cm was measured (diameter at soil level) and identified. The richest families were: Myrtaceae (nine), Solanaceae (six) and Aquifoliaceae (four). The Shannon Diversity Index in ST and CT sectors were respectively 2.73 and 2.31. The species with the highest importance values in CT sector were Solanum variabile, Piptocarpha angustifolia, Mimosa scabrella, Jacaranda puberula and Solanum pseudoquina. In ST sector, the species with highest importance values were Myrsine lorentziana, Casearia decandra, Cinnamodendron dinisii, Drimys brasiliensis and Ilex paraguariensis. The results showed that the synchronized bamboo die-off influenced the spatial variation in the floristic and structural descriptors of the tree species natural regeneration.

O presente trabalho teve como objetivo analisar a composição florística e a estrutura da regeneração natural em um setor onde ocorreu a mortalidade sincronizada de um maciço de taquara (Merostachys multiramea Hackel) (CT) e em uma área adjacente, com dossel contínuo e ausência de taquara (ST), em um fragmento de Floresta Ombrófila Mista Montana em Lages - SC. Foram alocadas 14 unidades amostrais de 5 x 5 m (seis no setor CT e oito no setor ST), nas quais todos os indivíduos arbóreos regenerantes com circunferência a altura do peito (CAP) ≤ 15 cm e altura ≥ 25 cm foram identificados e mensurados (diâmetro do colo). As famílias com maior riqueza de espécies foram: Myrtaceae (nove), Solanaceae (seis) e Aquifoliaceae (quatro). O setor ST apresentou um índice de diversidade de Shannon de 2,73 e o setor CT apresentou o valor de 2,31. Solanum variabile, Piptocarpha angustifolia, Mimosa scabrella, Jacaranda puberula e Solanum pseudoquina foram as espécies de maior valor de importância (VI) no setor CT. As espécies de maior VI no setor ST foram Myrsine lorentziana, Casearia decandra, Cinnamodendron dinisii, Drimys brasiliensis e Ilex paraguariensis. Os resultados mostraram que a mortalidade sincronizada de indivíduos de taquara influenciou na variação espacial dos descritores florísticos e estruturais da regeneração natural de espécies arbóreas.
Tree species natural regeneration after a massive bamboo die-off in an araucaria forest fragment in Lages, Santa Catarina State
Keywords: Merostachys multiramea; Regenerative component; Phytosociological descriptors; Merostachys multiramea; Componente regenerante; Descritores fitossociológicos